Albumin Exchange in Alzheimer's Disease: Might CSF Be an Alternative Route to Plasma? - Menendez-Gonzalez, Manuel; Gasparovic, Charles (Frontiers in Neurology, 2019)
Amyloid β (Aβ) in brain parenchyma is thought to play a central role in the pathogenesis of Alzheimer’s disease (AD). Aβ is transported from the brain into the plasma via complex transport mechanisms at the blood-brain barrier (BBB). About 90-95% of plasma Aβ may be bound to albumin. Replacement of serum albumin in plasma has been proposed as a promising therapy for AD. However, the efficacy of this approach may be compromised by altered BBB Aβ receptors in AD, as well as multiple pools of Aβ from other organs in exchange with plasma Aβ, competing for albumin binding sites. The flow of interstitial fluid (ISF) into cerebrospinal fluid (CSF) is another major route of Aβ clearance. Though the concentration of albumin in CSF is much lower than in plasma, the mixing of CSF with ISF is not impeded by a highly selective barrier and, hence, Aβ in the two pools are in more direct exchange. Furthermore, unlike in plasma, Aβ in CSF is not in direct exchange with multiple organ sources of Aβ. Here we consider albumin replacement in CSF as an alternative method for therapeutic brain Aβ removal and describe the possible advantages and rationale supporting this hypothesis.